Assessment and management of newly diagnosed classical Hodgkin lymphoma: a consensus practice statement from the Australasian Lymphoma Alliance. Issue 12 (22nd November 2021) - Cochrane, Tara; Campbell, Belinda A.; Gangatharan, Shane A.; Latimer, Maya; Khor, Richard; Christie, David R. H.; Gilbertson, Michael; Ratnasingam, Sumita; Palfreyman, Emma; Lee, Hui‐Peng; Trotman, Judith; Hertzberg, Mark; et al.
Abstract: The management of Hodgkin lymphoma (HL) has undergone significant changes in recent years. Due to the predilection of HL to affect younger patients, balancing cure and treatment‐related morbidity is a constant source of concern for physicians and patients alike. Positron emission tomography adapted therapy has been developed for both early and advanced stage HL to try and improve the outcome of treatment, while minimising toxicities. The aim of this review is to digest the plethora of studies recently conducted and provide some clear, evidence‐based practice statements to simplify the management of HL.